Pola Pengobatan pada Pasien Hipertensi dengan Diabetes Melitus Tipe 2 di RSUD Raden Mattaher Jambi - Lestari, Uce; Darwin, Deswinar; S, Lusiana Estiana (Jurnal Sains dan Teknologi Farmasi, 2011)
A Study on hypertension therapy with comorbidity of type II diabets mellitus at hospitalized patients of Internal Desease Ward Raden Mattaher Hospital Jambi descriptively by using prospective data has been conducted. Samples were taken by using cencus method from patients medical record from February to June 2011. Appropriatenes of drug use was evaluated based on criterions stated. Results showed that the most common an hypertension drugs used was captopril (55.33%) and anti-diabetic was reguler insulin (R1) (31.25%). The rationality of indication reched 97.10% of patients, medicine 100%, dosage 74.12%, dosage interval 80.65%, route of administration 100% and rational of time was 45.16%